Synthesis and human carbonic anhydrase I, II, VA, and XII inhibition with novel amino acid-sulphonamide conjugates - Hasan Küçükbay; Nesrin Buğday; F. Zehra Küçükbay; Andrea Ageli; Gianluca Bartolucci; Claudiu T. Supuran (Taylor & Francis Group, 2020)
A series of amino acid-sulphonamide conjugates was prepared through benzotriazole mediated coupling reactions and characterised by 1H-NMR, 13C-NMR, MS, and FTIR spectroscopic techniques as well as elemental analysis. The carbonic anhydrase (CA, EC 4.2.1.1) inhibitory activity of the new compounds was determined against four human (h) isoforms, hCA I, hCA II, hCA VA, and hCA XII. Most of the synthesised compounds showed effective in vitro CA inhibitory properties. The new amino acid-sulphonamide conjugates showed potent inhibitory activity against hCA II, some of them at subnanomolar levels, exhibiting more effective inhibitory activity compared to the standard drug acetazolamide. Some of these sulphonamides were also found to be effective inhibitors of hCA I, hCA VA, and hCA XII, with activity from the low to high nanomolar range.